Electronic Development Plan Deliberation: The Techniqie of Governmentalized - Fierda Nurany; Lutfia Nurul Hidayati (Spirit Publik: Jurnal Administrasi Publik, 2021)
The aims of this research were to find out the governmentality carried out by the Surabaya city government in implementing Development Plan Deliberation electronic. This was based on the Surabaya city government implementing governmentality that caused people to become apathetic. The theory used is the governmentality technique which explains that governmentality is built on three bases, namely 1) Governmentalized localities, 2) regulatory communities, and 3) Subject formation. The method of research uses a descriptive qualitative approach. Data collection methods conducted through in-depth interviews, secondary data, and field observations. The results showed that the technique of governmentalized localities is carried out by means of a development paradigm that the community is the main actor of development so that the citizens association level e- Development Plan Deliberation can decide on development proposals. Regulatory communities techniques are formed through social interaction between community representatives and village head in discussing the priorities of development planning proposals. While the formation of subjects is carried out by the village head by giving knowledge proposals so that the proposals are in accordance with the city development roadmap. In conclusion, the governmentality carried out by the Surabaya city government has had a good and bad impact on development planning. The impact is good, the community becomes more aware of the proposed development planning in the city of Surabaya, while the adverse effects of the community are apathetic because they are disappointed with their proposals which are often not approved